Scientific Atheism and the Problem of Divine Authority: A Historical–Philosophical Study of Theological Perspectives (Al-Qamar, 2026)
This study explores the intellectual conflict between scientific atheism and the concept of divine authority with description of Quranic theology. The aim of this article is to study the philosophical foundations of modern atheistic thought and to evaluate its claims in the light of the Quranic understanding of divine authority. The research adopts a historical-philosophical and analytical method, focusing on the development of scientific rationalism and the Quranic presentation of divine authority as an ultimate source of knowledge. The study argues that scientific atheism is primarily based on empirical methodology, which is limited in addressing metaphysical and existential questions, whereas the Quran establishes a comprehensive epistemological framework that integrates meaning, purpose and hope in human life. It is concluded that the tension between scientific atheism and Quranic theology emerges not merely from scientific discoveries but from the overlapping of their respective domains.
Keywords: Scientific Atheism, Divine authority, Quranic Theology, Religion and science, Philosophical Analysis